Reaching to Transgress: A Critical Self-Study of a Teacher Education Program. Issue 2 (February 2022) - Dansereau, Diana R.; Goodrich, Andrew; Hendricks, Karin S.; Smith, Tawnya D.; Vu, Kinh T.
Teaching to transgress, according to bell hooks, entails educators moving beyond an assembly-line approach to embrace integration of the mind, body, and spirit, and engaging in ways that honor the uniqueness of all students. The purpose of this study was to evaluate our music teacher education program in order to critically analyze how our practices may or may not transgress. In keeping with principles of S-STEP (Self-Study of Teacher Education Practices), we share the provocation for the study and its multiple overlapping stages. We present themes from the S-STEP process resulting from the data, and then reconsider those data using scholarly literature. Findings include the intellectual and spiritual growth of students and educators, and the challenges inherent in teaching to transgress within an online environment.